Prospects for the container shipping industry over the next 5 years - Soh, Jia Jie (2016)
In light of the recent stricter Sulphur emission level, container shipping companies have been looking into using LNG as an alternative fuel. As such, studying the impacts of using LNG fuelled container vessels is essential in assessing the prospect of container shipping industry. Factors such as Retrofit, New built, Fleet age and Governmental support were discussed with respect to how LNG fuel engines will affect container carrying capacity. Information from research papers and insights from interviews were used for this study. Results revealed that due to a lack of governmental support, the introduction of LNG would not have any impacts on the container carrying capacity in the next 5 years. However given sufficient amount of time, there would be an increasing governmental support, and the lower cost of LNG fuel compared to bunker fuel oil, will eventually lead to an increase in LNG fuelled container vessels. This will hence increase container carrying capacity, resulting in reduced freight rates in the future.